Pemberian Ekstrak Etanol Pelepah Batang Pisang Ketip Dapat Meringankan Polycystic Ovary Syndrome pada Tikus Putih Model - Mardika, Kadek; Sudatri, Ni Wayan; Sudirga, Sang Ketut (Jurnal Veteriner; Vol 23 No 2 (2022), 2022)
Polycystic ovary syndrome is a condition that affects the fertility of female reproductive organs. ketip banana pseudostem extract contains flavonoids, saponins, alkaloids, and vitamin C. It is known that ketip banana pseudostem extract can trigger cell proliferation and contain phytoestrogen compound. The purpose of this study was to determine the ability of ketip banana pseudostem extract on length of estrus cycle, histology structure and wight of reproductive organ, and estrogen hormone levels in white rats of PCOS model. White rats female Wistar strain aged 54 days used a total of 25 animals in this study. The treatment was given for 21 days by 1 ml/tail/day with the gavage method. Vaginal smear was began on 5th day of treatment every 12 hours/day for three estrus cycles (15 days). At the end of the study (21th day), the rats were dissected to take their ovaries and blood. The ovaries were weighed and then histological preparation with paraffin method and hematoxylin-Eosin staining. The parameters observed were length of estrus cycle, weight of ovary, number of ovary follicles, as well as estrogen hormone levels. The result of this study showed that ketip banana pseudostem extract can extend proestrus phases and estrus phases, increase estrogen hormone levels, increase corpus luteum number as significantly (p<0.05) on 150 mg/kgBW dosage.